Quality of Life among Elderly People and its Associated Factors in Makwanpur District: A Descriptive Cross-Sectional Study - Kharel, Sagun; Karkheti, Ashwin; Bajracharya, Anu; Paudyal, Laxmi; Kharel, Shree Krishna (Nepal Journal of Health Sciences, 2023)
Introduction: Aging is a universal process and it affects every individual, family, community, and society. It is a normal, progressive, and irreversible process. Objective: To assess quality of life among elderly people at old age home of Makwanpur district, Nepal. Methods: A descriptive cross-sectional study was conducted among 82 elderly people in old age home using complete enumeration sampling. A structured interview session was conducted by using WHOQOL-BREF tool. Data analysis was done in SPSS version 20 using descriptive statistics such as frequency, percentage, mean and standard deviation. Inferential statistics such as Chi square test was used to determine association. Results: Out of 82 respondents, majority of the respondents perceived QOL as neither poor nor good. Among total respondent’s, 36.6% were satisfied with overall perception of health. Also the study revealed the mean score was found higher in physical and psychological domain (50.609±11.75) and 50.304±12.13 respectively. The overall quality of life was found to be 71.292 which is good quality of life. There was significant association of age and religion with physical domain. Conclusions: The study concludes the overall quality of life was good among elderly. The mean score was found to be higher in physical and psychological domain in comparison to environmental and social relationship domain. Significant association was found in physical domain with age and religion.